2022
DOI: 10.3390/ijerph19084657
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Educational Intervention on Self-Care in Patients with Venous Leg Ulcers—A Randomized Controlled Trial

Abstract: Background: Although patients with venous leg ulcers are involved in ulcer management, little is known about why and how these patients self-treat their ulcers without direct supervision by health professionals. Yet patients’ knowledge of ulcer management can be important for achieving ulcer closure and/or preventing recurrence. This study thus investigates the effects of an educational intervention on knowledge of self-care among patients with venous leg ulcers, mainly on wound dressing practice, compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 54 publications
0
27
1
Order By: Relevance
“…Thirteen of them were published in English, and the other 3 were published in Chinese. Eleven of the studies came from Asia (4 in China, 29‐32 3 in Indonesia, 33‐35 2 in Iran, 36,37 1 in Singapore, 38 and 1 in India 39 ), 4 from Europe (one each from Ireland, 40 The Netherlands, 41 Croatia 42 and Germany 43 ) and 1 from South America (1 in Brazil 44 ). The total number of participants with chronic wounds was 1622.…”
Section: Results Of Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen of them were published in English, and the other 3 were published in Chinese. Eleven of the studies came from Asia (4 in China, 29‐32 3 in Indonesia, 33‐35 2 in Iran, 36,37 1 in Singapore, 38 and 1 in India 39 ), 4 from Europe (one each from Ireland, 40 The Netherlands, 41 Croatia 42 and Germany 43 ) and 1 from South America (1 in Brazil 44 ). The total number of participants with chronic wounds was 1622.…”
Section: Results Of Reviewmentioning
confidence: 99%
“…One study reported the participants' attitude toward compression therapy by self‐designed questionnaire and indicated that the educational intervention increased patients' awareness of compression therapy at post‐intervention follow‐up 42 …”
Section: Results Of Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Older age is inserted in this context due to the natural deficit of venous reflux observed with the aging process and the chronic diseases prevalent among older people [ 1 , 2 ]. Factors such as education and income can impact the development and evolution of VU, since they directly interfere with the individual’s level of self-care [ 20 ] as well as the financial capacity to fund the treatment of injuries, which usually requires substantial investment, depending on the technology used [ 21 , 22 ]. Therefore, we also analyzed whether sociodemographic variables could interfere with the correlations.…”
Section: Discussionmentioning
confidence: 99%